Peningkatan Produktivitas Kopi Arabika Gayo I dan II Berbasis Aplikasi Biourine dan Biokompos - Asis Asis; Rizki Ardiansyah; Rachman Jaya; Ishar Ishar (Institut Pertanian Bogor, 2020)
Gayo Highlands region had a potential area for the development of Arabica coffee because of the topographical conditions of the land that support the cultivation of Gayo Arabica coffee, but production of plants ranges from 650–750 kg ha-1, lower than some existing varieties which reach 1,5–2 tons ha-1. One way to increase production is the application of biourine and biocompost. This study aimed to determine the effect of the application of biourine and biocompost technology packages on the growth and production of Gayo I and II Arabica coffee plants. This study used a factorial separate plot design (RPT) consisting of Arabica Gayo I (A1) and Gayo II (A2) with a dose of NPK 150 kg ha-1 (farmer/control treatment) (C1), 150 mL-1 (biourine) + 5 ton ha-1 (biocompost) + NPK 100 kg ha-1 (C2), 125 mL plant-1 (biourine) + 7.5 ton ha-1 (biocompost) + NPK 100 kg ha-1 (C3), and 100 mL plant-1 (biocompost) + 10 ton ha-1 (biocompost) + NPK 100 kg ha-1 (C4). The results of the observations were analyzed by ANOVA and 95% DMRT. The results showed that the doses of biourine and biocompost fertilizers did not have interaction with Gayo I and Gayo II Arabica coffee, but for independent treatment of biourine and bicompost fertilizers, the dosage significantly affected the production of Gayo Arabica coffee. Application of 100 mL ha-1(biourine) + 10 tons ha-1 (biocompost) + 100 kg ha-1 NPK (C4) was able to increase the Gayo Arabica Coffee production by 41% when compared with NPK fertilizers of 150 kg ha-1 without biourine and biocompost (C1). Regression analysis showed that the level of 80% of Gayo Arabica Coffee was affected by the different application of biocompost dosages. Keywords: Arabica Gayo, biourine, biocompost, productivity